Snow white and the seven dwarfs: hello friend (Hello friend India, 2010)
Snow White, a beautiful princess, escapes her jealous stepmother and finds refuge with seven friendly dwarfs. The wicked queen disguises herself to poison Snow White with an apple. After a deep sleep, true love's kiss awakens her, leading to a happy ending.